Do the benefits of using calcitriol and other vitamin D receptor activators in patients with chronic kidney disease outweigh the harms?. Issue 3 (March 2017) - Toussaint, Nigel D; Damasiewicz, Matthew J
Abstract: The primary indication for administration of calcitriol or other vitamin D receptor activators (VDRA) in chronic kidney disease (CKD) is secondary hyperparathyroidism (SHPT). Prevention and treatment of SHPT appears important, as imbalances in mineral metabolism are associated with renal osteodystrophy, and higher parathyroid hormone (PTH) levels are associated with increased rates of mortality and morbidity in CKD patients. There is, however, a lack of controlled trial data that show lowering PTH with calcitriol/VDRA equates to improved clinical outcomes. Recent randomized controlled trials have concentrated on potential benefits of calcitriol/VDRA on cardiovascular outcomes and reduction of proteinuria and on possible differences between calcitriol and the various VDRA. Several systematic reviews and meta‐analyses have also been published, evaluating the benefits and harms of calcitriol/VDRA. Concerns have been raised about the effectiveness of calcitriol/VDRA for suppression of SHPT in the CKD stages 3–5 population, as well as potential adverse outcomes such as hypercalcaemia and elevation in FGF23 levels, suggesting their routine use to treat SHPT in the pre‐dialysis CKD population may not be favourable. Conversely, concerns still exist about the wide PTH range in advanced CKD, and that high values may negatively impact bone quality, result in the progression of parathyroid hyperplasia and decrease the effectiveness of treatments to reduce PTH. We discuss the current controversies relating to the challenges in the management of SHPT in patients with CKD stages 3–5 and the need for more evidence to determine the efficacy or harm of using calcitriol/VDRA in this population.